Cropping potential of forage soybean as a summer forage in Midwest U.S. rainfed systems - Baral, Rudra; Kim, Jiyung; Bhattarai, Bishwoyog; Koirala, Hari; Massigoge, Ignacio; Denson, Ethan; Guareschi, Cesar; Cominelli, Sofía; Rud, Joaquín Peraza; Bezerra de Oliveira, Jessica; Helguera, Paula Garcia; Ciampitti, Ignacio A.; et al. (Frontiers in Agronomy, 2025)
Rising feed and fertilizer costs, climatic uncertainties, and the summer slump in forage production are key challenges for livestock farmers in the Midwest region of the United States. Therefore, this study evaluated the dry matter yield (DMY), forage nutritive value (FNV), water use efficiency (WUE), and economic viability of forage soybean (Glycine max (L.) Merr) for the Midwest rainfed cropping system. The research aimed to assess the suitability of forage soybean as an alternative summer forage crop that is drought-resilient, require lower inputs, and provide higher yield and forage quality compared to traditional forages. A three-year field experiment (2020-2022) using a randomized complete block design with four replications assessed two planting dates (mid-May, early July) and four growth stages (V2, V3, R1, R3). DMY was significantly influenced by planting dates and growth stages, with optimum planting (mid-May) yielding an average of 13.9 ± 0.5 Mg ha-¹ at the R3 stage, surpassing late planting (early July) by 51%. Significant variations in FNV parameters were observed between optimum and late planting dates and across different growth stages. Late planting improved forage nutritive value (FNV), with lower acid detergent fiber (ADF) (26% vs. 31%), neutral detergent fiber (NDF) (30% vs. 35%), and lignin (6% vs. 7%), alongside higher in vitro dry matter digestibility (IVDMD) (84% vs. 79%) and relative forage quality (RFQ) (237 vs. 197) when harvested at the R3 stage. Crude protein remained stable (19–21%) across growth stages. Overall forage quality (RFV and RFQ) remained stable across growth stages (from V2 to R3), ensuring consistent quality and flexible harvest timing. The forage soybean demonstrated a WUE of 20 kg ha-¹ mm-¹ and a net profit of $336 with 32% return on investment per hectare. These results position forage soybean as a drought-resilient, high-yielding, high-quality, and economically viable alternative to traditional forages, addressing seasonal shortages and enhancing sustainability in rainfed systems. Further research, particularly animal feeding trials and long-term soil health impacts, is recommended to validate its potential for widespread adoption.